Efeitos de três programas de treino distintos incidentes no Ciclo Alongamento-Encurtamento (CAE) - Pedro Alexandre Valado Gonçalves (2018)
The term "plyometric" comes from the Greek Plyethein, which means "increase," and Metrique, which means "length." Plyometric training is a commonly used method to maximize strength production based on the use of the stretching-shortening cycle (SSC). This type of training is seen as the bridge between strength and power. This study aimed to determine the effects on the SSC of three different plyometric training programs with a duration of 11 weeks, being 3 of evaluation and 8 of training. Twenty-four students of the Sports Faculty of the University of Porto were involved in the study divided into 4 groups: Assisted Group (GA), Plyometric Group (GP), traditional group (GT) and control group (GC). Kruskal Wallis test of independent measures and Friedman of repeated measures were used to verify if there were significant differences between the groups on the different moments in the three variables studied. Later when the differences were detected the Mann Whitney was used to determine between which groups there were significant differences and Wilcoxon for the moments. The significance value was established in α ≤ 0.05. The results indicate that the three training programs have achieved significant improvements in the jump height and flight time variables. At the speed of takeoff, only the GP has achieved significant differences. Assisted and traditional groups improve the jump height and flight time; plyometric training group improves all variables studied. It was concluded that traditional training method promotes jump heights and flight times higher than assisted training.